The Role of Father Involvement in Predicting Aggressive Behavior among Juvenile Offenders in the Class I Medan LPKA - Winida Marpaung; Tio Nami Fachrainy Nauli; Maira Navisha; Florencia; Achmad Irvan Dwi Putra (Da'wa Faculty of Islamic State University Salatiga, 2026)
This study aims to examine the relationship between father involvement and aggressive behavior among adolescents in conflict with the law within the Indonesian Muslim socio-cultural context, where paternal responsibility and emotional guidance are emphasized in Islamic family values. In Islamic teachings, fathers are regarded as primary figures in nurturing, moral development, and emotional regulation of children, making their involvement an important protective factor against maladaptive behavior. This study involved 150 adolescents at the Class I Special Child Guidance Institution (Lembaga Pembinaan Khusus Anak/LPKA) in Medan using a total sampling technique. Data were collected using the Aggressive Behavior Scale and Father Involvement Scale, consisting of 37 and 42 items, respectively. Data were analyzed using Pearson Product-Moment correlation. The results showed a significant negative relationship between father involvement and aggressive behavior (r = -0.622, p < 0.05), indicating that higher father involvement is associated with lower aggressive behavior among adolescents. Father involvement contributed effectively 38.7% to aggressive behavior (R² = 0.387), while the remaining 61.3% was influenced by other factors. These findings suggest that strengthening paternal involvement may serve as an important preventive and rehabilitative factor in reducing adolescent aggression. Practically, the findings highlight the potential relevance of integrating Islamic family counseling and faith-based parenting interventions into juvenile rehabilitation programs to enhance father-child relationships and support adolescents’ socio-emotional development.